The association between tissue non-specific alkaline phosphatase expression and differentiation of mesenchymal stromal cells - Bartlett, Cara-Lesley (Stellenbosch : Stellenbosch University, 2017)
Thesis (D.Phil)--Stellenbosch University, 2017.